Analysis Of The Implementation Of The Merdeka Curriculum In 3t Areas (Underdeveloped, Frontier And Outermost) (Elementary School In Namohalu Esiwa Sub-District) - Maret Markus Harefa; Herlina Usman; Ika Lestari (Jurnal Elementaria Edukasia, 2024)
An merdeka curriculum is a curriculum approach that focuses on developing 21st century skills, student independence and community involvement in the learning process. The independent curriculum carries the concept of independent learning which gives schools, teachers and students the freedom to develop innovations, learn independently and show creativity. This research aims to analyse the implementation of the merdeka curriculum at SD Negeri 078452 Berua, SD Negeri 071162 Esiwa, and SD Negeri 280520 Kota Namohalu Esiwa. The research method used was qualitative with a phenomenological approach. Data analysis was conducted using the Miles and Hubermen model. Data analysis was conducted with reliability, transferability, depenability, and confirmability. The results showed that there was uniformity in several important aspects of the implementation of Merdeka Curriculum in the three public primary schools. This uniformity includes the opening of learning activities, variations in learning methods and media, structured learning planning, the use of formative and summative assessments, and monthly supervision. Despite the commitment of teachers and education stakeholders in improving the quality of learning, there is still a need for further improvement.